A Strongly Coupled Graphene and FeNi Double Hydroxide Hybrid as an Excellent Electrocatalyst for the Oxygen Evolution Reaction1. Issue 29 (6th June 2014) - Long, Xia; Li, Jinkai; Xiao, Shuang; Yan, Keyou; Wang, Zilong; Chen, Haining; Yang, Shihe
Abstract Cost‐effective electrocatalysts for the oxygen evolution reaction (OER) are critical to energy conversion and storage processes. A novel strategy is used to synthesize a non‐noble‐metal‐based electrocatalyst of the OER by finely combining layered FeNi double hydroxide that is catalytically active and electric conducting graphene sheets, taking advantage of the electrostatic attraction between the two positively charged nanosheets. The synergy between the catalytic activity of the double hydroxide and the enhanced electron transport arising from the graphene resulted in superior electrocatalytic properties of the FeNi‐GO hybrids for the OER with overpotentials as low as 0.21 V, which was further reduced to 0.195 V after the reduction treatment. Moreover, the turnover frequency at the overpotential of 0.3 V has reached 1 s−1, which is much higher than those previously reported for non‐noble‐metal‐based electrocatalysts.